Sex differences of fall-risk-increasing drugs in the middle-aged and elderly: a descriptive, cross-sectional study of FDA adverse event reporting system - Ying Zhao; Yuke Zhong; Liuqing Wu; Jiao Yan; Weitao Lu (Scientific Reports)
Abstract It’s well known that sex is a risk factor for the occurrence of adverse events (AEs), most of which have found sex differences. Real-world data studies on the sex differences of fall-risk-increasing drugs (FRIDs) are few and far between, with most small-scale retrospective studies based on FRID classes. To establish a list of FRIDs and describe their sex differences, we used preferred terms from the Medical Dictionary for Regulatory Activities to search for AEs in the FDA Adverse Event Reporting System (FAERS), and then perform disproportionality analyses and female/male ratio analyses. During January 2004 to March 2023, 101,746 fall-related AEs were reported in FAERS from patients aged 50 to 100, with 68,492 (67.3%) females and 32,547 (32.0%) males. We found 261 signals for females while 284 for males. For females, the top 3 signals with the highest reporting odds ratio (ROR) were anethole trithione, clopenthixol, nikethamide (ROR: 388.88, 212.10, 113.94), while the top 3 signals with the highest lower limit of information component (IC025) were nikethamide, anethole trithione, benzbromarone (IC025: 3.91, 3.15, 2.49). For males, the top 3 signals with the highest ROR were fluprednidene acetate, potassium hydroxide, ketazolam (ROR: 216.86, 108.43, 108.43), while the top 3 signals with the highest IC025 were clomethiazole, piribedil, melperone (IC025: 3.31, 3.24, 2.99). Moreover, among the 119 shared signals found between males and females, 33 were positively correlated with falls in females and 38 with falls in males. Signals showing significant sex differences were mainly concentrated on agents of the immune, nervous, musculo-skeletal, and cardiovascular systems. We offered a series of FRIDs and suggested their sex differences in falls through the FAERS. In the future, it is essential to balance the inclusion of women and men, and analyse sex-stratified for FRIDs.